Naphthalenones and isocoumarins of the fungus Ceratocystis fimbriata f. sp. platani - Bürki, N.; Michel, A.; Tabacchi, R. (Phytopathologia Mediterranea, 2003)
The chemical composition of the culture filtrates of Ceratocystis fimbriata f. sp. platani was investigated. Ten compounds potentially toxic to Platanus acerifolia were isolated and identified. These metabolites were mainly isocoumarins and naphthalenones. Three of these induced extensive necrosis on plane tree tissues.